IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK BERBASIS KURIKULUM MERDEKA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI MADRASAH - Ningsih, Putri Widya; Akhmansyah, Muhammad; Koderi; Sodiq, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Akidah Akhlak education plays a crucial role in shaping students' character. The Merdeka Curriculum offers pedagogical flexibility, enabling more interactive and experiential learning approaches. However, its implementation in Islamic schools (madrasah) encounters various challenges that require further investigation. This study employs a qualitative approach with a case study method at MTsN 1 Tanggamus. Data were collected through in-depth interviews, participatory observations, and document analysis involving teachers, the school principal, and students. Data analysis followed Miles and Huberman’s framework, encompassing data reduction, data display, and conclusion drawing. Findings reveal that Merdeka Curriculum-based Akidah Akhlak education significantly fosters students' religiosity, honesty, discipline, and responsibility. However, several challenges persist, including teachers' limited understanding of interactive methods, inadequate technological infrastructure, and insufficient parental involvement. While Merdeka Curriculum-based Akidah Akhlak education effectively nurtures students' character, its optimal implementation necessitates enhancing teachers’ pedagogical competence, improving learning facilities, and strengthening school-family collaboration. Further research with a broader scope is recommended to assess the long-term impact of this learning model.